PENGGUNAAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN BALAGHAH SEBAGAI UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA - Fathoni, Muhamad (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
ABSTRACT This study aims to improve students’ learning outcomes in the subject of Balaghah through the implementation of the Problem Based Learning (PBL) model. The background of this research is rooted in the low student engagement and academic performance, primarily caused by traditional teacher-centered teaching methods with minimal active participation. This research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted in two cycles consisting of four stages: planning, action, observation, and reflection. The research subjects were 25 eleventh-grade students at a Madrasah Aliyah. Instruments used included learning outcome tests, student activity observation sheets, and teacher performance observation sheets. The findings showed an increase in the average knowledge score from 55.00 (pre-cycle) to 67.00 (cycle II), and the mastery level rose from 16% to 75%. Additionally, there was a notable improvement in students’ attitudes—particularly in cooperation, honesty, accuracy, and responsibility—with an increase in the average score from 2.71 to 2.78 and affective mastery from 65.60% to 81.23%. PBL effectively promoted active, collaborative, and contextual learning, while also fostering students’ character development in critical thinking and accountability. These findings suggest that PBL is a viable and innovative alternative for teaching Balaghah, helping to overcome monotonous learning practices and significantly enhancing the quality of both cognitive and affective learning aspects. ABSTRAK Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa dalam mata pelajaran Balaghah melalui penerapan model Problem Based Learning (PBL). Latar belakang penelitian ini didasarkan pada rendahnya keterlibatan dan hasil belajar siswa yang disebabkan oleh pendekatan pembelajaran tradisional yang masih bersifat teacher-centered dan minim partisipasi aktif. Penelitian ini menggunakan pendekatan Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus, masing-masing terdiri atas empat tahap: perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah 25 siswa kelas XI di salah satu Madrasah Aliyah. Instrumen yang digunakan meliputi tes hasil belajar, lembar observasi aktivitas siswa, dan keterlaksanaan pembelajaran guru. Hasil penelitian menunjukkan adanya peningkatan nilai rata-rata pengetahuan dari 55,00 (pra-siklus) menjadi 67,00 (siklus II), serta peningkatan ketuntasan belajar dari 16% menjadi 75%. Selain itu, terjadi peningkatan pada aspek sikap siswa, terutama dalam hal kerja sama, kejujuran, ketelitian, dan tanggung jawab, dengan rata-rata skor sikap meningkat dari 2,71 menjadi 2,78 dan ketuntasan sikap dari 65,60% menjadi 81,23%. PBL terbukti efektif mendorong pembelajaran aktif, kolaboratif, dan kontekstual, serta membentuk karakter siswa yang kritis dan bertanggung jawab. Temuan ini menunjukkan bahwa PBL layak diterapkan dalam pembelajaran Balaghah sebagai alternatif inovatif yang mampu mengatasi pendekatan monoton dan meningkatkan kualitas pembelajaran dari aspek kognitif maupun afektif.